Design and Development Graphical User Interface on Inertial Navigation System of Submarine - Khoiro, Amirotul; Arifin, Imam; Pratama, Mahardhika; Adianto, M. Fajar (IPTEK Journal of Proceedings Series, 2019)
This paper discusses an underwater vehicle named Kapal Tempur Bawah Air (KTBA). This vehicle needs INS and GPSÂ  to know attitude, orientation, acceleration, velocity, and position. INS can provide attitude and movement data as well as long distance. INS on KTBA is implemented using Sublocus inertial sensor developed by Advanced Navigation. To know the navigation data, needed a process called interfacing. This process need a processor to read the data from inertial sensor. The processor to be used is Raspberry Pi 3 Model B. Besides data processing, need a user interface for the process that occurred. Therefore, this paper designed a Graphical User Interface for inertial navigation system. This interface design uses PyQt libraries with Python programming. The GUI testing is done by calculating the frame rate per second. The test results have different 56.83 % between Personal Computer and Raspberry Pi.